Studi Empiris Pengaruh Jumlah Uang Beredar Terhadap Pertumbuhan Ekonomi Indonesia Tahun 2015-2024 - sinaga, epelima_sinaga; Sitohang, Mizael Demak; Lita Br Sitepu, Agnes Dea; Harahap, Evi Syuriani (Universitas Negeri Surabaya, 2025)
The purpose of this study is to determine the effect of the amount of money in circulation on Indonesia's Economic Growth during the period 2015 to 2024. The data used is secondary data taken from the official publication of the Central Statistics Agency (BPS). The quantitative research method with a simple linear regression approach is applied to examine the relationship between independent and dependent variables. The test results indicate that the Amount of Money in Circulation has a positive and significant effect on Economic Growth, with a regression coefficient of 0.750 and a significance level below 0.05. This finding emphasizes the importance of managing the amount of money in monetary policy to support sustainable economic growth without causing the risk of excessive inflation.